Diplomasi Nabi Muhammad SAW dalam Membangun Kejayaan Umat - Muqoddam Cholil; Ahmad Faris (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article discusses the diplomacy of the Prophet Muhammad PBUH as a model of political communication, conflict resolution, and the development of civilization of the people. This study is important because prophetic diplomacy is often understood only as a historical event, even though it contains principles of negotiation, conflict control, respect for treaties, and peace preaching strategies that are relevant to contemporary society. The purpose of this research is to explain the pattern of diplomacy of the Prophet Muhammad PBUH in the pre-prophetic phase, the da'wah phase of Makkah, and the state phase of Medina. The research uses a qualitative method based on literature studies with a historical-normative approach. The main data are taken from the Qur'an, hadiths, the book of sirah, and modern academic literature on diplomacy, the charter of Medina, and the Treaty of Hudaibiyah. The results of the study show that the Prophet's diplomacy is built on the principles of trust, patience to listen, deliberation, respect for the interlocutor, commitment to agreements, and long-term benefit orientation. The event of the laying of Hajar Aswad, the dialogue with Quraish figures, the Charter of Medina, and the Hudaibiyah Agreement show his capacity as a spiritual leader as well as a statesman. This article concludes that prophetic diplomacy is a model of public communication ethics and conflict resolution that is able to transform tribal communities into civilized people.